(3CfhGQ GdJfRjd hCSQGQ GdJChjds - (3GdHjVGhj, CHh SYjO, CHh GdNjQ, fGUQ GdOjf, YHO Gddg Hf YeQ Hf eMeO Hf Ydj(B685(3g`s
(3ChdgG (B:s
(3ShQI GdfMd eGFI hYTQhf KeGfj (B( (3cPG (B) (3BjI ecjI aEfgG fRdJ HGdLRjI HYO bJd HSe Gddg GdQMef GdQMje (B: (3CJi CeQ Gddg adG JSJYLdhg cGfhG jSJYLdhf eG ChYOge GdQShds
(3BNQgG (B:s
(3ef GdLfI hGdfGS (B: (3HjGf ddhShGS Ch ddPj Ch eJYdb HjhShS Cj jhShS aj UOhQge ef bQC ShQI GdeYhPJjf acCfeG bQC GdcJH GdJj CfRdgG Gddg JYGdi cdgG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 110s
(3eYLe GdeDdajf (B2 / 266s
(3cTa GdXfhf (B1 / 186s
(3TPQGJ GdPgH (B5 / 392s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs